Perancangan Interior CafÃ© Playground di Surabaya - Febrina, Sherly; Honggowidjaja, Stephanus Pantja (Intra, 2019)
The growth of the cafe business is so rapid in Indonesia, there are many innovations in cafes that have sprung up such as cafes with library, cafes with co-working space. But for Surabaya itself, there are no cafes with playground innovations even though the playground cafe is an interesting innovation and in demand especially by people who are already married and have children. Therefore, buildings with the theme of eat, play and learn can be one solution for parents who want to take a break from routine or relieve fatigue but still carrying out their duties in parenting. This building is expected to be able to combine dining, playing and education facilities to support the activities of parents and children as their interactions.